2021
DOI: 10.1136/bmjsem-2021-001106
|View full text |Cite
|
Sign up to set email alerts
|

Low but not high exercise systolic blood pressure is associated with long-term all-cause mortality

Abstract: ObjectivesThe risks associated with achieving a high peak systolic blood pressure (SBP) during clinical exercise testing remain controversial, although this issue has not been evaluated in relation to predicted SBP standards. This cohort study aimed to evaluate the long-term risk of all-cause mortality in males in relation to reference values of peak SBP and the increase in SBP during exercise from the Fitness Registry and the Importance of Exercise: A National Database (FRIEND).MethodsWe followed 7164 males (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(47 reference statements)
3
5
0
Order By: Relevance
“…Second, ≈25% of community-dwelling individuals in our study exhibited peak SBP values above existing clinical thresholds, but some of these individuals achieved high peak SBP due primarily to greater cardiac-peripheral performance. These findings in relation to cross-sectional physiological measures are therefore in concert with other studies showing that high peak SBP may not be a good predictor of adverse outcomes at the population level, 42 raising the prospect of using CPET (or imaging-based measures of stroke volume/cardiac performance) to clarify the physiological determinants and relevance of a high peak exercise SBP. Third, we observed that BP measures that account for workload (eg, BP at a fixed workload, or the SBP/W slope) were directly related with higher arterial stiffness and lower cardiac-peripheral performance.…”
Section: Discussionsupporting
confidence: 75%
“…Second, ≈25% of community-dwelling individuals in our study exhibited peak SBP values above existing clinical thresholds, but some of these individuals achieved high peak SBP due primarily to greater cardiac-peripheral performance. These findings in relation to cross-sectional physiological measures are therefore in concert with other studies showing that high peak SBP may not be a good predictor of adverse outcomes at the population level, 42 raising the prospect of using CPET (or imaging-based measures of stroke volume/cardiac performance) to clarify the physiological determinants and relevance of a high peak exercise SBP. Third, we observed that BP measures that account for workload (eg, BP at a fixed workload, or the SBP/W slope) were directly related with higher arterial stiffness and lower cardiac-peripheral performance.…”
Section: Discussionsupporting
confidence: 75%
“…Considered independently, the meaning of peak SBP values during exercise testing remains uncertain with studies finding both an increased (28,29) and a decreased (30,31) risk of mortality with elevated SBP during exercise. Although the SBP values of 210 and 190 mm Hg for males and females, respectively, are generally recognized as the upper thresholds of healthy SBP responses to exercise (32), Hedman et al (33) recently found that low, not high, peak SBP, in reference to established age- and sex-specific peak SBP reference values, was associated with an increased risk of all-cause mortality in adult males. Therefore, an elevated but not overly exaggerated increase in SBP at peak exercise may reflect healthy systolic cardiac function and the integrity of the surrounding vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Although our recent publications evaluated the outcome related to peak SBP [2,4], we do not by any means reject the clinical value of using submaximal SBP to determine the risk of adverse outcome in patients undergoing exercise testing. In contrast, submaximal SBP has the advantage of indirectly considering work rate, especially if the submaxi-mal work rate is standardized [5].…”
mentioning
confidence: 83%